Food systems sustainability and environmental policies in modern economies - Obayelu, Abiodun Elijah, 1972- (Engineering Science Reference, 2018)
"This book explores the complex relationship between production resources, agricultural and food systems, environmental policies and food security has become important in order to be able to sustain and secure the future. It outline principles for developing more specific solutions that are adaptable to local realities"--Provided by publisher.